The Effectiveness of Mask Required Regulations for Congregants at Jami Mosque In Gowa District Perspective Saddu Zari'ah - Abdul Halim Talli; Lomba Sultan (Jurusan Ilmu Hukum Fakultas Syariah dan Hukum uin alauddin, 2022)
This study raises the issue of how effective the Regional Regulations are Obligatory to Wear Markers for the Jami Mosque Congregation in Gowa Regency Saddu Zari'ah's Perspective. From this main problem, it is limited to sub-problems, namely how the effectiveness of the local regulation on the obligation to wear masks for jami mosque congregations in Gowa Regency, as well as how saddu zari'ah's perspective on the mandatory wearing of masks. This study aims to find out the effectiveness of the local regulation on the mandatory wearing of masks for jami mosque congregations in Gowa Regency, and to find out the saddu zari'ah perspective on the mandatory wearing of masks. This descriptive-qualitative field research uses a juridical-syar'iy approach, by collecting data through questionnaires and in-depth interviews for religious leaders, administrators and jami mosque congregations, the data is processed, analyzed to produce conclusions. The results of this study indicate that the local regulations that require wearing masks are effective for jami mosque congregations in Gowa Regency. As many as 74.4% of jami mosque congregations in Gowa Regency always wear masks outside the home, including at the mosque. The effectiveness of the use of masks is based on several reasons: 1) the congregation knows that wearing masks has been required by the government through local regulations, 2) similarly that with the saddu zari'ah method, the regional regulations that require wearing masks are in accordance with Islamic law